2018
DOI: 10.1007/s00125-018-4709-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of the ankle–brachial index on the development of micro- and macrovascular complications in individuals with type 2 diabetes: the Rio de Janeiro Type 2 Diabetes Cohort Study

Abstract: A low ABI is associated with excess risk of adverse cardiovascular outcomes, mortality and peripheral neuropathy development or worsening, and improves cardiovascular risk stratification. The ABI should therefore be routinely evaluated in individuals with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…As for the microvascular complications, Lee et al found a twofold risk of retinopathy in persons with altered ABI, defined as ABI values of <0.9 or ≥1.3,48 similar to the risk of neuropathy reported by Cardoso et al , and both being slightly higher than our results 15. Cardoso et al did not find a relation of low ABI with retinopathy or renal outcomes,15 whereas in our study, low ABI was significantly associated with all the microvascular outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As for the microvascular complications, Lee et al found a twofold risk of retinopathy in persons with altered ABI, defined as ABI values of <0.9 or ≥1.3,48 similar to the risk of neuropathy reported by Cardoso et al , and both being slightly higher than our results 15. Cardoso et al did not find a relation of low ABI with retinopathy or renal outcomes,15 whereas in our study, low ABI was significantly associated with all the microvascular outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in patients with diabetes obtained higher estimates for mortality and cardiovascular events than our study. For all-cause mortality, HRs of 2.01–2.10 were observed in participants with low15 26 and high ABIs26; for MCEs, an HR of 2.5 was estimated 15. However, lower risk figures have also been reported in these patients (with diabetes).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There were several methods for DPN diagnosis, we classified in four groups: a) >2 clinical signs, including nine studies [48,49,54,56,58,64,71,72,75]; b) >2 clinical signs and symptoms, including 14 studies [50, 52, 53, 57, 59-61, 63, 65, 66, 68-70]; c) >2 clinical signs + nerve conduction test (NCT), including one study [55]; and d) only NCT or sudomotor disfunction test, including four studies [51,62,67,74]…”
Section: Search Resultsmentioning
confidence: 99%